2017
DOI: 10.9734/ijpss/2017/34527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pinching and Paclobutrazol on Growth, Flowering, Anatomy and Chemical Compositions of Potted Geranium (Pelargonium zonal L.) Plant

Abstract: Aims: A two-year field trials were carried out during the two successive seasons of 2015 and 2016 to study the effect of pinching and paclobutrazol (PP 333) at 20, 40 and 60 ppm on growth, flowering, histological characteristics and chemical compositions of potted Pelargonium zonale L. plant. Methodology: Uniform terminal cuttings were planted in 8 cm plastic pots containing 1:1 mixture of peat moss and sand. On March 1 st of 2015 and 2016, uniform well rooted cuttings were repotted in 20 cm diameter plastic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…In case of dry weight of the flowers, PBZ application has not shown any significance difference (P=0.0976) on Henckelia Royal Queen plants. Hence, the present result disagreed with Sharaf-Eldien et al (2017) in Zinnia elegans and Abd El-aal and Mohamed (2017) in Pelargonium zonal about the effect of PBZ on dry weight of the flowers on Henckelia Royal Queen plants. But, due to the analyzed data, plants showed that there was remarkable difference (P=0.0006) due to interaction of pinching and PBZ on dry weight of Henckelia Royal Queen plants.…”
Section: Dry Weight Of Single Flowercontrasting
confidence: 99%
See 1 more Smart Citation
“…In case of dry weight of the flowers, PBZ application has not shown any significance difference (P=0.0976) on Henckelia Royal Queen plants. Hence, the present result disagreed with Sharaf-Eldien et al (2017) in Zinnia elegans and Abd El-aal and Mohamed (2017) in Pelargonium zonal about the effect of PBZ on dry weight of the flowers on Henckelia Royal Queen plants. But, due to the analyzed data, plants showed that there was remarkable difference (P=0.0006) due to interaction of pinching and PBZ on dry weight of Henckelia Royal Queen plants.…”
Section: Dry Weight Of Single Flowercontrasting
confidence: 99%
“…At 13 th WAT, both pinched and non-pinched plants were shown increased number of flowers in PBZ treated plants when compared with PBZ 0 ppm applied plants. But Abd El-aal and Mohamed (2017) mentioned that the increase of number of flowers per plant of Pelargonium zonale L. plants is proportional with the increment of paclobutrazol concentration in the two seasons and interactions between pinching and paclobutrazol concentrations statistically increased the flowers number per plant, hence the highest number of flowers per plant was recorded by pinched plants sprayed with highest PBZ concentration due to the nature of PBZ effects on the prolongation of the vegetative and reproductive growth of Tabernaemontana coronaria Stapf plants. Since, increasing the endogenous level of cytokinin by PBZ led to increasing the formation of leaves as well as the number of branches per plant.…”
Section: Number Of Flowersmentioning
confidence: 99%
“…At the age of 28 and 56 dap the decrease in light intensity of 75% and 50% gives the same chlorophyll content results with a light intensity of 100% at all concentrations of paclobutrazol (0 ppm, 40 ppm, 80 ppm and 120 ppm). An increase in the concentration of paclobutrazol at all intensities gives a value of chlorophyll content equal to the concentration of paclobutrazol 0 ppm (El-Aal & Mohamed, 2017). The addition of paclobutrazol 0 ppm at a light intensity of 75% and 50% results in chlorophyll content equal to the light intensity of 100% and paclobutrazol 0 ppm.…”
Section: Chlorophyll Contentmentioning
confidence: 94%
“…El-Bably (2008) revealed that high concentrations of PBZ reduced plant height, fresh and dry weights of vegetative parts and roots, root length, total carbohydrates, but increased phenol and indole contents of Anisacanthus wrightii. Abd El-Aal and Mohamed (2017) reported that foliar spraying with PBZ caused a decrement in plant height and leaf area of Pelargonium zonale plants, this was accompanied with an increase in the number of branches/plant.…”
Section: Total Indoles (Mg/100 G Dw) and Phenols (%)mentioning
confidence: 99%